Turnover stability of shuttlecocks - transient angular response and impact deformation of feather and synthetic shuttlecocks - Lin, C. S. H.; Chua, C. K.; Yeo, J. H. (Procedia Engineering, 2013)
This paper looks at the impact deformation and turnover stability of both feather and synthetic shuttlecocks using a racket based launcher. Flight of a shuttlecock can be described by steady state and unsteady state. Previous works were mainly focused on the steady state flight. While bulk of flight is in the steady state, the transient unsteady state is critical because it determines the initial condition of stabilized flight. The whole phase of rapid angular change during the unsteady state is the turnover process. Impact deformation and turnover response were studied with a racket-based launcher. Angles of attack with respect to time were recorded using high speed capturing. While the resultant plot showed significant variations between shuttles, most completed turnover process within 0.05s to 0.06s. Despite inherent disadvantage in density of the skirt material, turnover stability of synthetic shuttlecock was not compromised. All shuttles exhibited under damped behaviour in angular response and a 2nd order approximation was identified for the mean response of each. Feather shuttles have higher damping factor and smaller natural period. Higher-grade feather shuttle was observed to maintain skirt structural integrity better than lower tier shuttle in the impact deformation testing. Skirt stiffness is desirable to prevent deformation upon impact at higher racket speed. The practice grade feather shuttle displayed deformation pattern akin to a blooming flower, while the top grade shuttle was able to resist impact deformation at same racket speed. In conclusion, higher-grade shuttles could resist skirt deformation from racket-shuttle impact and attain steady state flight within a shorter time.